Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait - Chim, C. K.; Tong, Samantha J. W. (Zootaxa, 2019)
This study describes a new genus and new species of Tanaidacea that was collected from inside the tests of dead Tetraclita barnacles in Singapore. Xenosinelobus n. gen. is most similar to Sinelobus but can be distinguished by the (1) unusually short antennal fifth article, (2) tooth-like lacinia mobilis on right mandible, (3) long terminal seta on epignath, (4) plumose inner seta near dactylus insertion on cheliped propodus, (5) spiniform seta on pereopod 1 coxa, (6) presence of setae on inner margins of pereopod 1 propodus and dactylus, (7) claw-like terminal articles on pereopods 2 and 3, (8) row of setulose and flattened denticulate setae along distal margin of pereopod 6 propodus, (9) dorsal seta on claws of pereopods 4–6, (10) complete row of dorso-transverse setae on pleonites 1 and 2, (11) one seta on pleopod basis outer margin, (12) two or three setae on pleopod endopod inner margin and (13) three-articled uropod with final article 1.6 times as long as preceding article. A new diagnosis and key to genera is provided for the subfamily Sinelobinae.